Pengaruh Dosis Iradiasi Gamma terhadap Pengurangan Bobot Cabai Rawit sebagai Teknologi Pengawetan Makanan - Ariyanti, Dhita; Megasari, Kartini; Ridho, Ridho; Adeska, Rieka Arkaninto; Akbar, Sulhamdi (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
Food technology as a source of human needs must receive a special attention. Various methods in pursuing food preservation technology are carried out in order to have a long shelf life. This study aims to reduce the percentage of weight loss of cayenne pepper through gamma irradiation technology. The research method used in the process of preserving pepper is gamma exposure irradiation at varying doses (1; 1.5; 2; and 2.5 kGy). Based on the research results, it can be concluded that gamma irradiation at doses of 1; 1.5; 2; and 2.5 kGy affected the weight loss of cayenne pepper. The 8th to 10th days of observation showed the highest percentage of weight loss which ranged from 5.58% to 18.71%, from the original (31.69% without gamma irradiation). Intracellularly, this means that there is a disruption of the fungal membrane in cayenne pepper which causes leakage of sugar and protein from damaged cells. In addition, irradiation disrupts the metabolic function of malate dehydrogenase (MDH) and succinate dehydrogenase (SDH) in the tricarboxylic acid cycle (TCA). This study was tested statistically with a single ANOVA, showing that gamma irradiation affected the weight loss of cayenne pepper as proved by the result of Fcrit (6.725) > Ftable (3.8852).